2013
DOI: 10.1111/jfd.12078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fixation methods for demonstration of Neoparamoeba perurans infection in Atlantic salmon, Salmo salar L., gills

Abstract: Formaldehyde-based fixatives are generally employed in histopathology despite some significant disadvantages associated with their usage. Formaldehyde fixes tissue by covalently cross-linking proteins, a process known to mask epitopes which in turn can reduce the intensity of immunohistochemical stains widely used in disease diagnostics. Additionally, formaldehyde fixation greatly limits the ability to recover DNA and mRNA from fixed specimens to the detriment of further downstream molecular analyses. Amoebic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, previously published articles show that histological techniques as well as proteomic and genomic techniques work with PAXgene-fixed tissues. [7][8][9][10] The possibility of detecting parasite DNA in DNA extracted from PFPE salmon gills 11 suggests that in future experiments, virus RNA, DNA, and proteins may be easily detected in PFPE tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previously published articles show that histological techniques as well as proteomic and genomic techniques work with PAXgene-fixed tissues. [7][8][9][10] The possibility of detecting parasite DNA in DNA extracted from PFPE salmon gills 11 suggests that in future experiments, virus RNA, DNA, and proteins may be easily detected in PFPE tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In proteomic and genomic assays, proteins and nucleic acids derived from PAXgene-fixed, paraffin-embedded (PFPE) tissues react as those derived from fast frozen tissues. [7][8][9][10] Recently, Cadoret et al 11 showed that DNA isolated from PAXgene-fixed tissue of Atlantic salmon gills could be used to detect Neoparamoeba perurans DNA by polymerase chain reaction (PCR). Also, conventional histological staining and immunohistochemistry (IHC) could be performed on PAXgene-fixed tissue to visualize the amoeboid parasite in salmon gills.…”
Section: Introductionmentioning
confidence: 99%
“…It is recognised that the histological gill score may have been influenced by the buffered formalin fixative used in this study. The use of an alternative fixa- tive such as Davidson's may have resulted in higher retention of amoebae on the gills sampled (Cadoret et al 2013); however, it was more practical to use buffered formalin which is also routinely used in fish histopathology. The sensitivity of the real-time assay was demonstrated by the fact that positive fish were already detected by Week 12 (10% of fish tested were positive), and by Week 16, all fish tested were positive for N. perurans.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after PGD scoring, fish were bled and the gill arch with the highest PGD score was excised for both transcriptome profiling and histopathological examination. For transcriptomic profiling, 3 transverse sections (gill arch ∼3 mm long with 3-4 pairs of filaments) from dorsal, medial and ventral regions of the gill (Figure 1) were transferred to RNAlater R (Sigma-Aldrich, St. Louis, MO, United States), kept at (Cadoret et al, 2013) for 24 h, followed by a short-term exposure to 10% neutral buffered formalin before tissue processing for histopathological examination.…”
Section: Sampling and Gross Morphologymentioning
confidence: 99%